Muhammadiyah Sebagai Gerakan Islam dan Pendidikan - Mar'ati Zarro; Yunani Yunani; Aulia Novemy Dhita (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
Muhammadiyah is an Islamic movement with the Da’wah Amar Makruf Nahi Munkar, Islamic aqidah and based on the Qur’an and Sunnah. Muhammadiya was founded by K.H. A. Dahlan on Dzulhijjah November 18th 1912 AD in Yogyakarta. Muhammadiyah developed extensively. In just a few years, many branches Muhammadiyah established in Srandakan, Wonosari, Imogiri, and several other areas. Its development of Muhammadiyah got resistance from the Dutch East Indies. The establishment of Muhammadiyah education is based on theological motivation that a perfect degree of faith and devotion will be able to be achieved by the people if they have the knowledge depth. A sense of nationalism will develop if each individual citizen obeys the laws, then puts forward the obligations before claiming their rights. This can then be achieved if every citizen has a high discipline and love the motherland.